Competition in the African air transport market - Tassew Dufera Tolcha (Transportation Research Interdisciplinary Perspectives, 2024)
The air transport market in Africa is regulated and viable for designated carriers. Although there are some sub-regional liberalizations, airlines primarily compete based on the specifications of bilateral air service agreements. However, this competitive landscape has not been thoroughly investigated. This study examines market concentration in the African aviation industry and explores its impact on the output of African airlines. The competition was measured at the airport level using the Herfindahl-Hirschman index. Panel data were drawn from 54 countries, 339 airports, and 221 airline groups for the period 2015–2019. Kernel density estimation shows that the region’s market for air transport services is fragmented, with many small airlines. Strong competition is more prevalent at larger hub airports, airports near tourist destinations, and major airports far from larger African hubs, while markets tend to be concentrated where dominant and protected flag carriers operate. Competition is also low or limited at smaller airports offering limited flights. The results of panel regression analysis reveal a nonlinear relationship between market concentration and airline output, as strong competition may limit airlines’ output, and high concentration may promote a dominant airline or alliance that may hinder other airlines from entering or remaining in the market.